Pelaksanaan Redistribusi Tanah Eks Hak Guna Usaha - Zaenal Arifin; Nikmatul Wachidah (Al-Adl : Jurnal Hukum, 2023)
This study aims to analyze the implementation of land redistribution of ex-use rights(HGU) as well as to analyze the constraints and solutions for implementing the land redistribution in Semarang Regency. One of the problems in the land sector in Indonesia is that there is still an imbalance in terms of land ownership which is still controlled by the owners of capital. There are still many farmers who do not own land that can be managed to improve farmer's health. In order to realize equal distribution of land ownership and increase the welfare of farmers, the government implemented a land redistribution program for ex-HGU lands that have expired and whose permits have not been extended. HGU permit for PT. Sinar Kartasura, which is located in Candi Village and Kenteng Village, Semarang Regency, has used its permit to become an object of agrarian reform as part of the government's efforts to reduce the imbalance of land ownership between farmers/people and capital owners.This research uses a normative juridical approach with the support of primary data. The research data uses primary legal materials such as laws and regulations on agrarian affairs and secondary legal materials which include books and journals that study agrarian reform. The results of this study explain that the priority for implementing agrarian reform is for ex-HGU and HGB land whose HGU has expired and within 1 year has not submitted an application for a permit extension. the implementation of land redistribution in Candi Village and Kenteng Village, Semarang Regency, as many as 3.26i of ex-HGU plots of PT. Sinar Kartasura has successfully completed 100%. Utilization of ex-HGU land is still used as agricultural land. Obstacles encountered in land redistribution are limited human resources and limited time to complete land redistribution. The recommendation from this study is that the participation of the public and the private sector in supporting the implementation of land redistribution will realize optimal and sustainable implementation of agrarian reform.